Assessing the Effectiveness of Teacher Training Programs to Improve the Quality of School Education in Nepal - Subedi, Bhawani Shankar (Journal of Training and Development, 2015)
Inadequate transfer of knowledge, skills, attitudes and behaviours from the training environment to the workplace environment has emerged as a global issue. Teachers’ training has not been an exception. Available literature on teacher training indicates that the contribution of training can be assessed at least on six dimensions- quality, access, equity, efficiency, teacher development and overall school development. Studies conducted in the area of teacher training or teacher professional development in the context of Nepal are also evident of lack of sufficient transfer of knowledge and skills from training to workplace. There are several factors facilitating or inhibiting the extent of such transfer. Research shows that the training of teachers has contributed and can positively influence quality of education if stakeholders are made aware of and well informed about the quality and relevance of training and development interventions carefully designed and implemented for the capacity development of teachers, teacher educators or trainers. This article has been derived from the synopsis of a comprehensive study conducted in Nepal and concluded in March 2010. Data bases of 4033 trained teachers of 45 schools from 25 sample districts were studied. This study was a blending of quantitative as well as qualitative approaches. Nine education experts and 22 field researchers were involved. The author was the team leader of the study. The only academic purpose of this article is to inspire excellence in teaching, learning and performance by means of professionalism and capacity building of teachers, teacher trainers and their employers. DOI: http://dx.doi.org/10.3126/jtd.v1i0.13084 Journal of Training and Development Vol.1 2015: 9-14